2013
DOI: 10.1158/1535-7163.targ-13-a252
|View full text |Cite
|
Sign up to set email alerts
|

Abstract A252: A phase 1 study of ARRY-382, an oral inhibitor of colony-stimulating factor-1 receptor (CSF1R), in patients with advanced or metastatic cancers.

Abstract: Introduction: Within the tumor microenvironment, CSF1R signaling is thought to play an important role in recruitment and differentiation of tumor-associated macrophages and osteoclasts, promoting disease progression through suppression of anti-tumor immune response, promotion of angiogenesis, tumor cell metastasis and tumor-induced osteolysis. ARRY-382 is a potent, highly selective, oral inhibitor of CSF1R. This Phase 1 dose-escalation study was designed to determine the maximum tolerated dose (MTD) and to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 0 publications
4
22
0
Order By: Relevance
“…The inhibitors tested included the highly selective CSF1R inhibitors GW-2580 ( n = 197) (GlaxoSmithKline) and ARRY-382 ( n = 131) (Array BioPharma), the latter of which has completed Phase I clinical testing. Both inhibitors exhibit a high degree of specificity for CSF1R across the kinome, including other class III receptor tyrosine kinases (Figure 1B ) [ 25 , 26 ]. We observed that a proportion of CLL specimens showed sensitivity to these selective CSF1R inhibitors, with 25.9% (51/197) and 27.5% (36/131) of specimens showing sub-micromolar IC50s (the concentration of inhibitor required to reduce viability to 50%) for GW-2580 and ARRY-382, respectively (Figure 1C-1D ).…”
Section: Resultsmentioning
confidence: 99%
“…The inhibitors tested included the highly selective CSF1R inhibitors GW-2580 ( n = 197) (GlaxoSmithKline) and ARRY-382 ( n = 131) (Array BioPharma), the latter of which has completed Phase I clinical testing. Both inhibitors exhibit a high degree of specificity for CSF1R across the kinome, including other class III receptor tyrosine kinases (Figure 1B ) [ 25 , 26 ]. We observed that a proportion of CLL specimens showed sensitivity to these selective CSF1R inhibitors, with 25.9% (51/197) and 27.5% (36/131) of specimens showing sub-micromolar IC50s (the concentration of inhibitor required to reduce viability to 50%) for GW-2580 and ARRY-382, respectively (Figure 1C-1D ).…”
Section: Resultsmentioning
confidence: 99%
“…3; Table 2). These drugs were well tolerated in phase I trials, also when combined with paclitaxel [85,86]. Moreover, emactuzumab, a CSF1R-antibody, decreased CD163+ TAMs infiltration in serially collected tumor biopsies of patients with various solid tumors, including breast cancer [86].…”
Section: Csf1-csf1r Inhibitionmentioning
confidence: 99%
“…No objective responses were observed. [24] A phase Ib trial of ARRY382 plus pembrolizumab (anti-PD-1 antibody) is ongoing.…”
Section: Arry382mentioning
confidence: 99%